Reformas na educação médica no Brasil : estudo comparativo entre as diretrizes curriculares nacionais dos cursos de graduação em medicina de 2001 e 2014 - Rocha, Vinícius Ximenes Muricy da (2018)
This paper deals with a qualitative research, of a documentary nature, addressing a comparative analysis between Resolution CNE / CES nº 4 of November 7, 2001 and Resolution No. 3 of June 20, 2014, which deal with the National Curricular Guidelines (DCN) of the Undergraduate Medical Courses. These documents are responsible for the official character that reforms in medical education in the country have been occurring since the beginning of the 2000s, in order to deepen the relationship between medical education and the Unified Health System (SUS). The DCN 2014 arose under the advent of the More Doctors Program, based on the provisions of Law 12,871, of October 22, 2013. This law, which is the target of controversy and attacks by various sectors of political society, media and medical corporation, seeks Update the country's medical education to the changes that have occurred in Brazil's health and education public policies in the last 15 years, in the sense of guidelines that include access to social rights, equity, qualification of public services, changes in health care policies, social inclusion and Democratization of higher education. Thus, the objective of the study is to analyze the relationships between the DCN 2001 and the 2014, taking into account their continuities, differences, innovations and established changes; 2- Reflect on the meanings that similar or related concepts of medical education used in different epochs take on historical contexts marked by different temporalities; 3- To elaborate notes on the potential of innovation / change / transformation of the proposals presented by the DCN 2014. For this purpose the Content Analysis was used as analysis methods, with reference in Bardin and Franco; And the History of Concepts, with a reference in Koselleck and Marçal Brandão. As conclusion, the work shows an important conceptual and normative effort of the new DCN 2014, which seeks to induce Brazilian medical schools to move from a level of innovations to changes, in the reformist sense that this new device presents itself. However, the success of such a policy will depend on a number of objective conditions, which involve the risk of retrogression in social policies after the approval of Constitutional Amendment 55/2016, and the eventual stagnation of the country's social policies, including in the health and education sectors, As well as the interference that the external relations of the sectors of opposition to the Mais Médicos Program will be able to have in the scope of the medical schools in the country. Consequently, the work points to the importance of the continuity of research that evaluates the concrete implementation of the new DCNs, in the sense of materializing what it advocates in its scope, as well as problematizes the need for a critical understanding in the incorporation of the pedagogy of competences as element Structuring of medical training in each course, since it can reproduce an individualistic logic of learning construction, potentially ""capable"" by the liberal logic that permeates hegemonic ideology in the corporate organization processes of medical practice in Brazil. That is, there will be no change or transformation.